Non-isentropic release of a shocked solid - Heighway, P; Sliwa, M; McGonegle, D; Wehrenberg, C; Bolme, C; Eggert, J; Higginbotham, A; Lazicki, A; Lee, H; Nagler, B; Park, H; Rudd, R; et al. (American Physical Society, 2019)
We present molecular dynamics simulations of shock and release in micron-scale tantalum crystals that exhibit postbreakout temperatures far exceeding those expected under the standard assumption of isentropic release. We show via an energy-budget analysis that this is due to plastic-work heating from material strength that largely counters thermoelastic cooling. The simulations are corroborated by experiments where the release temperatures of laser-shocked tantalum foils are deduced from their thermal strains via in situ x-ray diffraction and are found to be close to those behind the shock.